Benign Fibrous Histiocytoma of the Lung: A Case Report - Rosa, Rita (2024)
A fibrous histiocytoma is a benign tumoral lesion generally localized in the dermis or the superficial subcutaneous tissue. Fibrous histiocytoma of the lung is a very rare tumor, with only a few cases in the literature. We present a case of a 48-year-old man, asymptomatic, with a solitary pulmonary nodule with a high metabolism in PET/TC. Given the location and suspicious hypermetabolism in PET/TC, the patient underwent a wedge resection, with pathological examination concluding on a primary benign fibrous histiocytoma of the lung. Fibrous histiocytoma of the lung can be a difficult diagnosis, with a non-specific clinical history as well as radiologic findings. Hence, histopathological examination remains vital in establishing a definitive diagnosis. Prognosis is generally excellent, as these tumors usually have low recurrence rates after complete excision.